Analysing Revitalised Security Industry: The Tech-Powered Transformation for Small States - Pulami, Manish Jung (Unity Journal, 2024)
This scholarly endeavour delves into the extensive metamorphosis undergone by the security industry, a consequence of profound technological advancements. In particular, the study discerns the strategic utilisation of the tech-powered revitalised security industry by certain small states as a means to transcend the confines of defensive nihilism. An identified gap in current scholarship lies in the limited exploration of the transformative dynamics associated with technological innovation-driven security industries within the context of small states. Consequently, this paper endeavours to furnish a comprehensive analysis of the revitalised security industry and its multifaceted implications on the domains of security, politics, and economics. The research employs a nuanced approach, with a primary emphasis on case studies pertaining to Israel and Singapore, both exemplifying small states that have strategically harnessed high-tech capabilities to defy conventional perceptions of their inherent limitations. The central objective is to scrutinise the methodologies adopted by these small states, offering insights into their concerted efforts to bolster technological prowess. This divergent trajectory challenges prevailing realist assumptions regarding the inherent constraints imposed upon small states. Methodologically, the study employs a diverse array of analytical tools, including case study techniques, policy discourse investigation, and cross-case comparative analysis. This eclectic methodological approach aims to discern and unravel the intricate interplay between technology’s transformative influence on the security industry and its subsequent ramifications for small states.